2017
DOI: 10.14814/phy2.13361
|View full text |Cite
|
Sign up to set email alerts
|

Aging modifies the effect of cardiac output on middle cerebral artery blood flow velocity

Abstract: An association between cerebral blood flow (CBF) and cardiac output (CO) has been established in young healthy subjects. As of yet it is unclear how this association evolves over the life span. To that purpose, we continuously recorded mean arterial pressure (MAP; finger plethysmography), CO (pulse contour; CO‐trek), mean blood flow velocity in the middle cerebral artery (MCAV; transcranial Doppler ultrasonography), and end‐tidal CO 2 partial pressure (PetCO 2) in healthy young (19–27 years), middle‐aged (51–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…Aging is associated with a decline in cerebral blood flow and resting brain metabolism 17,18 . With aging, brain perfusion becomes increasingly dependent on cardiac output irrespective of cerebrovascular autoregulatory integrity 19 . The finding of the current study that cerebral blood flow may be compromised in patients with severe cardiac dysfunction is supported by prior studies that found patients with severe heart failure had considerably lower cerebral blood flow than healthy age‐matched controls 20,21 .…”
Section: Discussionsupporting
confidence: 70%
“…Aging is associated with a decline in cerebral blood flow and resting brain metabolism 17,18 . With aging, brain perfusion becomes increasingly dependent on cardiac output irrespective of cerebrovascular autoregulatory integrity 19 . The finding of the current study that cerebral blood flow may be compromised in patients with severe cardiac dysfunction is supported by prior studies that found patients with severe heart failure had considerably lower cerebral blood flow than healthy age‐matched controls 20,21 .…”
Section: Discussionsupporting
confidence: 70%
“…By design the subjects were healthy individuals exposed to simulated bleeding which restrains us from extrapolating the data to elderly subjects, considering that with healthy aging brain perfusion becomes increasingly dependent on cardiac output (Bronzwaer et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…The large increase in systolic blood pressure during exhaustive exercise challenges CBF control mechanisms including cerebrovascular or cerebral autoregulation, the cerebrovascular responsiveness (CVR CO2 ) to carbon dioxide (CO 2 ) and oxygen (O 2 ) partial pressures, matching of local cerebral blood supply to the metabolic demand (i.e., neurovascular coupling), neurogenic control ( Immink et al, 2014 ; Ritz et al, 2014 ; Willie et al, 2014 ; Phillips et al, 2016 ), and maintenance of cardiac output ( Ide et al, 1998 , 1999a ; Van Lieshout et al, 2001 , 2003 ; Ogoh et al, 2005a ; Bronzwaer et al, 2014 , 2017 ). During exercise, CBF increases as quantified by several methods (for review, see Secher et al, 2008 ; Smith and Ainslie, 2017 ).…”
Section: Autonomic Neural Control Of Cbf During Exercisementioning
confidence: 99%